A randomized double-blind placebo-controlled clinical trial of nitazoxanide for treatment of mild or moderate COVID-19. (March 2022) - Rossignol, Jean-François; Bardin, Matthew C.; Fulgencio, Jessica; Mogelnicki, Dena; Bréchot, Christian
Summary: Background: There is an urgent need for treatments of mild or moderate COVID-19 in an outpatient setting. Methods: A randomized double-blind placebo-controlled clinical trial in 36 centers in the U.S. between August 2020 and February 2021 investigated the safety and effectiveness of oral nitazoxanide 600 mg twice daily for five days in outpatients with symptoms of mild or moderate COVID-19 enrolled within 72 h of symptom onset (ClinicalTrials.gov NCT04486313). Efficacy endpoints were time to sustained clinical recovery (TSR, a novel primary endpoint) and proportion of participants progressing to severe illness within 28 days (key secondary). Findings: 1092 participants were enrolled. 379 with laboratory-confirmed SARS-CoV-2 infection were analyzed. In the primary analysis, median (IQR) TSR were 13·3 (6·3, >21) and 12·4 (7·2, >21) days for the nitazoxanide and placebo groups, respectively ( p  = 0·88). 1 of 184 (0·5%) treated with nitazoxanide progressed to severe illness compared to 7 of 195 (3·6%) treated with placebo (key secondary analysis, odds ratio 5·6 [95% CI 0·7 - 46·1], relative risk reduction 85%, p  = 0·07). In the pre-defined stratum with mild illness at baseline, nitazoxanide-treated participants experienced reductions in median TSR (3·1 days, p  = 0·09) and usual health (5·2 days, p  < 0·01) compared to placebo. Nitazoxanide was safe and well tolerated. Interpretation: Further trials with larger numbers are warranted to evaluate efficacy of nitazoxanide therapy in preventing progression to severe illness in patients at high risk of severe illness and reducing TSR in patients with mild illness. Funding: This research was supported by Romark, Tampa, Florida USA.